Definition of the Leadership Formation Process for Undergraduate Nursing Students - Edison Kabak (Indonesian Journal of Global Health Research, 2026)
Leadership is an essential capability that nurses must develop to provide safe, collaborative, and ethically grounded care. Nonetheless, undergraduate nursing students often differ in how they perceive the developmental process of leadership, which may influence their preparedness to navigate future professional challenges. This study seeks to uncover how nursing students interpret their journey in developing leadership within the academic and clinical learning environment. Using an 8-participant phenomenological design, researchers conducted in-depth interviews with ten students actively engaged in both academic and organizational roles. Data were examined using Colaizzi’s analytical steps to identify core themes that reflect participants’ lived experiences in cultivating leadership. The analysis revealed four central themes: (1) leadership as a continuous learning experience, (2) the role of self-reflection and professional accountability, (3) social interaction and organizational participation as avenues for leadership growth, and (4) moral and ethical foundations as pillars of leadership integrity in nursing. The findings indicate that leadership development among nursing students is an evolving and multifaceted process shaped by hands-on experience, reflective thinking, and internalized ethical values. Students view leadership not merely as directing others but as an ongoing self-development process characterized by professionalism, empathy, and social responsibility. Leadership growth is layered, progressive, and intertwined with educational experiences, reflective practices, and engagement in ethically oriented organizations, forming future nurses with strong, reflective, and humanistic leadership qualities.